Deeper insights into the drug defense of glioma cells against hydrophobic molecules - Verebova, Valeria; Belej, Dominik; Joniova, Jaroslava; Jurasekova, Zuzana; Miskovsky, Pavol; Kozar, Tibor; Horvath, Denis; Stanicova, Jana; Huntosova, Veronika (International journal of pharmaceutics, 2016)
By means of fluorescence microscopy the intracellular distribution of fluorescent drugs with different hydrophobicity (quinizarin, emodin and hypericin) was studied. Selective photoactivation of these drugs in precisely defined position (nuclear envelope) allowed moderately hydrophobic emodin enter the nucleus. Highly hydrophobic hypericin was predominantly kept in the membranes with no fluorescence observed in the nucleus. The redistribution of quinizarin, emodin and hypericin between lipids, proteins and DNA was studied in solutions and cells. Based on these results was proposed theoretical model of hydrophobic drugs' nuclear internalization after photo-activation. Molecular docking models showed that hypericin has the strongest affinity to P-glycoprotein involved in the cell detoxification. Presence of 10 μM quinizarin, emodin or hypericin increased P-glycoprotein function in U87 MG cells. Moreover, emodin pretreatment allowed quinizarin nuclear internalization without photo-activation, which was not the case for hypericin. The synergy of such pretreatment and photo-activation should lessen the drug doses with simultaneous increase of drug efficacy triggering cell apoptosis/necrosis.
Keywords: anthrachinony; gliom; Hydrophobic and Hydrophilic Interactions; LDL-cholesterol; Anthraquinones; Anthracenes; Cell Line, Tumor; Emodin; Cholesterol, LDL; simulace molekulového dockingu; nádorové buněčné linie; DNA; lidé; Cell Nucleus; Perylene; P-glykoprotein; Selective photo-activation; Hypericin; ATP Binding Cassette Transporter, Subfamily B, Member 1; perylen; Glioma; sérový albumin; Light; buněčné jádro; P-glycoprotein; anthraceny; Antraquinones; Glioma cells; hydrofobní a hydrofilní interakce; Serum Albumin; světlo; Molecular Docking Simulation; emodin; Humans